The Body Speaks: Reading Literary Stagings of Embodied Expressions of Trauma and Its Violent Return - Festus, Tammy-Leigh (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2024.